Effects of Substance Use on Retention of Learners in Schools in Northern City Division, Mbale City - Clemesia Kabuni (Uganda Christian University, 2024)
This study investigated the effects of substance use on learner retention in Northern City Division, Mbale City. It examined the relationship between substance use frequency and mental health issues among school-age children, the influence of media on substance experimentation and academic performance, and the impact of peer influence on learner retention rates. A mixed-methods approach was employed, incorporating quantitative surveys and qualitative interviews with students, parents, teachers, and community leaders. To analyze the relationship between substance use frequency and mental health issues, a one-way Analysis of Variance (ANOVA) was conducted. Substance use frequency was categorized into low, moderate, and high levels, while mental health issues were assessed using a scale reflecting symptoms such as anxiety and depression. The ANOVA compared the mean mental health scores across these categories to identify significant differences. The null hypothesis posited no significant difference in mean mental health scores among the different substance use frequencies, while the alternative hypothesis suggested that at least one group's mean differed significantly. The ANOVA results, including an F-value and a p-value, indicated statistically significant differences (p < 0.05), leading to the rejection of the null hypothesis. This demonstrated that substance use frequency significantly affected mental health, with higher frequencies correlating with more severe mental health issues. The study highlighted the significant impact of frequent substance use on mental health and academic performance, alongside the roles of media exposure and peer influence. It emphasized the effectiveness of school-based educational programs and media literacy interventions, although their impact varied. Recommendations included comprehensive strategies to address media influence and peer interactions, with suggestions for further research on regional differences and policy impacts to improve student retention and reduce substance use.